64.6k views
5 votes
ANSWER QUICK SHOW WORK!
1. 4(1-3x)+7x=9
2. 9-5x=12-(6x+7)

User Flypig
by
5.0k points

2 Answers

3 votes

Answer:

1.) x = -1

2.) x = -4

Explanation:

1.) 4(1 - 3x) + 7x = 9

=> Use distributive property:

4 - 12x + 7x = 9

=> Combine like terms:

4 - 5x = 9

=> Isolate 5x:

-5x = 5

=> Isolate x:

x = 5/-5

=> Simplify:

x = -1

2.) 9 - 5x = 12 - (6x + 7)

=> Use distributive property:

9 - 5x = 12 -6x - 7

=> Combine like terms:

9 - 5x = 5 - 6x

=> Isolate x to one side:

9 + x = 5

x = -4

Hope this helps!

User Foo Stack
by
5.0k points
6 votes
1. 4(1 - 3x) + 7x = 9

Distribute

4 - 12x + 7x = 9

Isolate x terms

-12x + 7x = 9 - 4

Combine like terms

-5x = 5

Divide

x = -1

2. 9 - 5x = 12 - (6x + 7)

Distribute

9 - 5x = 12 - 6x - 7

Move terms to get x terms on one side

-5x + 6x = -9 + 12 - 7

Combine like terms

x = -4
User Jason Roman
by
5.5k points